PENGARUH TEPUNG AMPAS KECAP SEBAGAI SUBSTITUSI TEPUNG IKAN DALAM PAKAN TERHADAP PERTUMBUHAN DAN NILAI KECERNAAN JUVENIL IKAN KERAPU MACAN (Epinephelus fuscoguttatus) - Muhammad Marzuqi; Nyoman A. Giri; Eva Agustina; Ketut Suwirya (Jurnal Perikanan Universitas Gadjah Mada, 2008)
The aim of the study was to know the effect of soy sauce waste as substitution of fish meal in diet on the growth and dietary nutrient digestibility of juvenile tiger grouper (Epinephelus fuscoguttatus). The experiment used completely random design (CRD) with six treatments and three triplicates. The initial body weight of juvenile tiger grouper was 4.03 g and total length of 5-7 cm reared in 18 polycarbonate tanks with each 30 liter volume. Each of tanks was equipped with aeration and flow through water system. Six formulated diet with dry pellet form containing different level of soy sauce waste as substitution of fish meal, i.e., 0%, 7%, 14%, 21%, 28% and 28% added 0.15% methionine amino acid were teste. The result showed that the utilization of soy sauce waste as substitution fish meal influenced absolute growth, specific growth rate, feed conversion ratio and protein retention (P<0.05), but not significantly different (P>0.05) on survival rate of juvenile tiger grouper. Dietary nutrient digestibility (protein) obtained 98.05- 99.69%. Dietary nutrient digestibility decreased with utilization of soy sauce waste in diet. These experiments concluded that the utilization of soy sauce waste as substitution of fish meal could be used until optimal limit 21%, while the substitution of 28% can’t used for diet formulation for tiger grouper (Epinephelus fuscoguttatus).